2010
DOI: 10.1111/j.1540-8175.2009.00982.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Left Ventricular Systolic Asynchrony in Patients with Clinical Hypothyroidism

Abstract: Patients with overt hypothyroidism show evidence of LV asynchrony by TSI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 46 publications
0
31
0
Order By: Relevance
“…Recently, we have reported the presence of LV asynchrony in overt hypothyroidism [37]. However, both hyperthyroidism and hypothyroidism leads to many changes in blood pressure, cardiac output and contractility, myocardial oxygen consumption [2,38].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have reported the presence of LV asynchrony in overt hypothyroidism [37]. However, both hyperthyroidism and hypothyroidism leads to many changes in blood pressure, cardiac output and contractility, myocardial oxygen consumption [2,38].…”
Section: Discussionmentioning
confidence: 99%
“…Overt hypothyroidism impairs early and late regional and global diastolic peak longitudinal LV strain rates (35,36). In addition, tissue Doppler-derived e' and the e'/a' ratios are reduced, and the myocardial performance index may be prolonged (37).…”
Section: Discussionmentioning
confidence: 99%
“…Dyssynchrony was first emphasized in the early studies in systolic HF patients with low EF and wide QRS complex, however, 1/3 of HF patients with a narrow QRS complex were found to exhibit substantial mechanical dyssynchrony as well . Recently, systolic dyssynchrony was not only detected in the patients with symptoms of HF and preserved EF but also in hypertension, diabetes mellitus, acute myocardial infarction, and hypo‐ and hyperthyroidism . Recent studies revealed that systolic dyssynchrony is an important co‐determinant of progression and exacerbation of HF …”
Section: Discussionmentioning
confidence: 99%